A Comparative Analysis of Medical and Islamic Sharia Perspectives on Underage Pregnancy - Andriana, Kusuma; Putri Ayuningtyas, Aulia; Siti Nurzulia, Isnaini (Jurnal Ilmu Kedokteran Keluarga, 2025)
Pregnancy among females under 19 is a global health crisis impacting adolescents' biological, psychological, social, and spiritual well-being. It carries high risks of medical complications, such as anemia and preterm birth, alongside considerable emotional and social stress. Within Muslim societies, this issue also involves moral and Islamic legal dimensions, highlighting the necessity of preserving personal dignity and ensuring legitimate lineage. This systematic review, following PRISMA 2020 guidelines, collected literature from 2020–2025 using keywords "adolescent pregnancy," "medical approach," and "Islamic ethics." Results from 23 publications indicate that early pregnancy is a multidimensional issue. The medical approach focuses on biological risks and the importance of reproductive education. In contrast, the Islamic perspective emphasizes moral protection and preventing adultery through the principles of maqāṣid al-syarī‘ah (preservation of life, ḥifẓ al-nafs, and preservation of progeny, ḥifẓ al-nasl). The study concludes that integrating the bio-psycho-social model with Islamic bioethics provides a comprehensive, holistic approach. It is essential to implement religion-based reproductive education and policies aligned with Islamic ethical principles for effective prevention of early pregnancy